Quantitative Studies of the Lung of the Domestic Fowl (Gallus gallus var. domesticus) - Vidyadarayan, M.K.; King, A. S; Kassim, H. (1988)
Comprehensive quantitiative studies on the lung of the domestic fow, (Gallus galluf var. domesticus). have been made. The data obtained were VL/W 14.65 ± 3.17 cm3/kg; Sa/W 18.08 ±2.51 cm2 /g; rht 0.322 ± 0.01 um; Dto/W 12. 79 ± 2.20 mlo/minlmmHglkg; dan DLo/W 1.39 ± 0.36 mlo/minlmmHglkg. These values are compared with those reported by other authors, and possible reasons for the differences are discussed. The mean values for many of the parameters have been calculated so that the values so obtained may form a basis for further investigations.